Proceso de atención de denuncias y acciones del organo de Control Institucional - Figueroa Sánchez, Armando Edgardo (2021)
The article aimed to analyze the association of the process of receiving, evaluating and handling complaints, with the subsequent ex officio action of the institutional control body in the Local Educational Management Unit, Ica 2020 Region. The methodological approach was quantitative, not experimental. , with a linear descriptive-correlational design, the applied questionnaire had the participation of 69 directors of educational institutions in the Ica Region. Concluding that the process of receiving, evaluating and handling complaints is significantly associated with the subsequent ex officio action of the institutional control body in the Local Educational Management Unit. This is reflected in the opinion of the managers, that is, to the extent that the processes for receiving, evaluating and handling complaints are efficient, the subsequent ex officio actions will be favorable.